002 Detecting retinal changes in autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) using optical coherence tomography (OCT). Issue 3 (9th February 2012) - Giunti, P; Nethisinghe, S; Clayton, L M; Vermeer, S; Chapple, J P; Reilly, M M; Bremner, F
Abstract : Background: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS; OMIM 270550) is an early-onset inherited neurodegenerative disorder caused by mutations in the SACS gene and characterised by cerebellar ataxia, spasticity and peripheral neuropathy. Retinal changes may also be associated with ARSACS. Objective: To determine the usefulness of optical coherence tomography (OCT) to measure retinal nerve fibre layer thickness in ARSACS. Methods: A full ophthalmological evaluation, including OCT, was performed in a patient with ARSACS in whom we identified two novel SACS mutations. OCT was also performed in family members of the proband. Results: OCT demonstrated marked retinal nerve fibre layer thickening in the proband, and also in two out of the three unaffected carriers. Conclusions: OCT appears to be a sensitive tool for identifying retinal changes even in carriers with SACS mutations. We suggest the use of OCT in evaluating patients with suspected ARSACS.